Irony, Prosody, and Social Impressions of Affective Stance. Issue 2 (7th February 2020) - Mauchand, Maël; Vergis, Nikos; Pell, Marc D.
ABSTRACT: In spoken discourse, understanding irony requires the apprehension of subtle cues, such as the speaker's tone of voice (prosody), which often reveal the speaker's affective stance toward the listener in the context of the utterance. To shed light on the interplay of linguistic content and prosody on impressions of spoken criticisms and compliments (both literal and ironic), 40 participants rated the friendliness of the speaker in three separate conditions of attentional focus (No focus, Prosody focus, and Content focus). When the linguistic content was positive ("You are such an awesome driver!"), the perceived critical or friendly stance of the speaker was influenced predominantly by prosody. However, when the linguistic content was negative ("You are such a lousy driver!"), the speaker was always perceived as less friendly, even for ironic compliments that were meant to be teasing (i.e., positive stance). Our results highlight important asymmetries in how listeners use prosody and attend to different speech-related channels to form impressions of interpersonal stance for ironic criticisms (e.g., sarcasm) versus ironic compliments (e.g., teasing).